2003
DOI: 10.3386/w9677
|View full text |Cite
|
Sign up to set email alerts
|

Do Demographic Changes Affect Risk Premiums? Evidence from International Data

Abstract: We examine the link between equity risk premiums and demographic changes using a very long sample over the twentieth century for the US, Japan, UK, Germany and France, and a shorter sample covering the last third of the twentieth century for fifteen countries. We find that demographic variables significantly predict excess returns internationally. However, the demographic predictability found in the US by past studies for the average age of the population does not extend to other countries. Pooling internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…However, Poterba (2001) argues, after exploiting a variety of demographic measures, that no significant relationship between demographic structures and stock returns (or the stock price) has been detected. Additionally, Ang and Maddaloni (2005) have claimed that no significant relationship was found for US data, although the proportion of retired consumers has been shown to have a significant negative impact on stock returns based on international data. Brooks (2007) has reported that no strong historical relationship has been found between the demographic structure and the aggregate stock price, particularly for countries with strong stock market participation.…”
mentioning
confidence: 99%
“…However, Poterba (2001) argues, after exploiting a variety of demographic measures, that no significant relationship between demographic structures and stock returns (or the stock price) has been detected. Additionally, Ang and Maddaloni (2005) have claimed that no significant relationship was found for US data, although the proportion of retired consumers has been shown to have a significant negative impact on stock returns based on international data. Brooks (2007) has reported that no strong historical relationship has been found between the demographic structure and the aggregate stock price, particularly for countries with strong stock market participation.…”
mentioning
confidence: 99%
“…They demonstrated that housing demand significantly increases for the age group 20-35 years and then declines for subsequent age groups. An adequate number of empirical studies provide plausible arguments that demographic structure, specifically ageing population, could have a significant negative impact on financial asset prices, supporting the claim that demographic changes influence asset prices (Ang & Maddaloni, 2005;Bae, 2010;Brooks, 2002;Davis & Li, 2003;Geanakoplos, Magill, & Quinzii, 2004;Goyal, 2004;Jamal & Quayes, 2004;Park, 2010;Quayes & Jamal, 2016;Saita, Shimizu, & Watanabe, 2016;Yoo, 1994). Yoo (1994), using a multi-country OLG model, examined the relationship between age distribution and real asset returns and established how demography can generate low frequency price movements.…”
Section: Literaturementioning
confidence: 88%
“…Der Anstieg des Durchschnittsalters führt dabei zu einer Erhöhung der Risikoprämie. Ang und Maddaloni (2005) haben letzteres jüngst zwar für die USA bestätigt, für andere OECD-Länder konnten sie jedoch keinen stabilen Zusammenhang finden. Zusammenfassend kann man deshalb feststellen, dass zwar theoretisch und empirisch einiges für einen künftigen Anstieg der Risikoprämie spricht, aber diese Prognose mit beträchtlicher Unsicherheit behaftet ist.…”
Section: Implikationen Für Die Entwicklung Der Risikoprämieunclassified